ANALISIS PENGARUH TRAIT KEPRIBADIAN DAN SOCIAL INFLUENCE TERHADAP SIKAP PEMBELIAN IMPLUSIF (Studi Kasus pada Mahasiswa Institut Agama Islam Hasanuddin Pare Kediri) - Arianto; Maftuhin (LPPM INSTITUT AGAMA ISLAM HASANUDDIN PARE, 2024)
Every living creature that God created certainly has different characteristics, including humans, who have character and behavior that reflect an image of life that is not the same as one another. Every individual definitely needs interaction with other individuals to influence each other in making choices. This research aims to find out how personality traits and social influence influence impulsive buying attitudes carried out on the Hasanuddin Pare Islamic Institute campus. This research is a type of quantitative research. The object of research in this thesis is student respondents aged 19-21 years who filled out the questionnaire as many as 23 people or 41%, at the age of 22-24 years as many as 22 people or 44%, and at the age >25 as many as 10 people or 15% so that it can It is known that the total number of respondents who filled out the questionnaire form was 55 students. The results of quantitative research where the respondent's score on personality traits through 5 indicators, namely Openness, Extraversion, Agreeableness, Neuroticism and Conscientiousness, was 3.4900, which can be interpreted as indicating that the personality traits experienced by students are in the tolerable category. The results of the research are that many students and students still do not understand each other's personalities, and there are still many who cannot control themselves from doing things that are not necessary. It is very important for a student to be able to understand his own personality traits and understand the social influences on him, so that the student can control his personality in making purchasing decisions.